Comparison of Sexual Function Changes in High-Risk and Normal Pregnancies - Özdemir, Özge; Bolluk, Gökhan; Kurt Bilirer, Kübra; Yüksel, Semra; Günal, Nurefsan (Cerrahpaşa Medical Journal, 2022)
Objective: The evidence on the sexual function in high-risk pregnancies is scarce. Sexual function generally decreases during pregnancy, although it decreases more in high-risk pregnancies. Therefore, we aimed to evaluate the sexual function changes in high-risk pregnancies compared to normal pregnancies. Methods: This observational case–control study included 200 pregnancies with high-risk and normal pregnancies, each consisting of 100 cases. Demographic and obstetric data were collected, and participants completed the Female Sexual Function Index. Results: Body mass index was found to be 28.6 ± 5.7 kg/m2 in high-risk and 26.3 ± 3.9 kg/m2 in normal pregnancies (P = .002). Gestational age was 28.1 ± 5.8 in high-risk and 27.3 ± 5.4 in normal pregnancies (P < .34). Education levels were found to be higher in high-risk pregnancies compared to normal pregnancies (P < .001). Previous cesarean delivery rates were higher in normal pregnancies compared to high-risk pregnancies (21% vs. 6%, P < .001). Most frequent comorbidities in the high-risk group were gestational diabetes mellitus (n = 38), preeclampsia (n = 21), intrauterine growth restriction (n = 13), and cholestasis (n = 8). The Female Sexual Function Index assessments revealed that the high-risk group had significantly higher rates of sexual dysfunction (80% vs. 68%, P < .001). Conclusion: The sexual function decreases during pregnancy; however, women with high-risk pregnancies have significantly higher rates of sexual dysfunction as compared with others having normal pregnancies. Therefore, Female Sexual Function Index, which is inexpensive and can be easily applied to high-risk pregnancies, may be important for timely interventions to improve the quality of life of these women in terms of sexual function. Cite this article as: Özdemir O, Bolluk G, Kurt Bilirer K, Yüksel S, Günal N. Comparison of sexual function changes in high-risk and normal pregnancies. Cerrahpaşa Med J. 2022;46(2):134-137.